The book : a cover-to-cover exploration of the most powerful object of our time - Houston, Keith, 1977- (W.W. Norton & Company, 2016)
We may love books, but do we know what lies behind them? Keith Houston reveals that the paper, ink, thread, glue, and board from which a book is made tell as rich a story as the words on its pages -- of civilizations, empires, human ingenuity, and madness. In a tactile history of this 2,000-year-old medium, Houston follows the development of writing, printing, the art of illustrations, and binding to show how we have moved from cuneiform tablets and papyrus scrolls to the hardcovers and paperbacks of today.